Numeracy musical training for school children with low achievement in mathematics - Arias Rodriguez, Indira; Mendes do Nascimento, Jessica; Voigt, Marcos Felipe; Dos Santos, Flávia Heloísa (Anales de Psicología / Annals of Psychology, 2019)
The present case-control, double-blind, and prospective study investigated the effects of Numeracy Music Training (NMT) on cognitive skills of primary school children. Participating in the study were 42 children aged 8 to 10 years divided into two groups: Low Achievement in Math (n = 21), and Average Achievement in Math (n = 21). The children underwent two evaluations before and after NMT, where cognitive tests and behavior scales were applied that assessed variables such as school performance, IQ, working memory, numerical cognition, anxiety and stress. NMT was developed in eight group sessions and aimed to stimulate the systems of numerical cognition and integrate basic musical knowledge, and symbolic representations. After the intervention, through musical training, the children in both groups showed significant improvements in school performance, systems of numerical cognition and working memory, as well as the reduction of manifestation of mathematics anxiety.